Prevalence of Cryptosporidium Infection in the Global Population: A Systematic Review and Meta-analysis - Dong, Shurong; Yang, Ya; Wang, Yingjian; Yang, Dongjian; Yang, Yu; Shi, Ying; Li, Chunlin; Li, Linhan; Chen, Yue; Jiang, Qingwu; Zhou, Yibiao (Acta parasitologica, 2020)
Background Cryptosporidium is a protozoan parasite that can infect both humans and animals and cause cryptosporidiosis. We aimed to estimate the global prevalence of Cryptosporidium infection. Methods In this study, Web of Science, Medline and PubMed were searched for relative articles, published between January 1, 1960 and January 1, 2018. Included articles were restricted to English language and that sample size of articles was not less than 50. Studies with no information on the study period, location, method of diagnosis, sample size and number of infected people were excluded. Studies about outbreak, laboratory report or immunocompromised population were excluded as well. The quality of the included publications was assessed. The prevalence of cryptosporidiosis was estimated by DerSimonian–Laird random-effects model, after converting by the Freeman–Tukey type double arcsine transformation. Findings From 13,064 publications selected by literature search, 221 studies were included in the meta-analysis. The global pooled prevalence of Cryptosporidium infection was 7.6 % (95% CI: 6.9–8.5). The highest estimated prevalence of Cryptosporidium infection was in Mexico (69.6%, 95% CI 66.3–72.8), Nigeria (34.0%, 95% CI 12.4–60.0), Bangladesh (42.5%, 95% CI 36.1–49.0) and Republic of Korea (8.3%, 95% CI 4.4–13.2) among general residents, patients, school children and healthy population, respectively. The estimated prevalence was high in people from low-income country, people with gastrointestinal symptoms, people younger than 5 years old and residents not living in urban areas. Conclusions These estimates indicate the substantial prevalence of Cryptosporidium infection in the world, which may provide a theoretical basis for the formulation of the prevention strategy about Cryptosporidium .